2001
DOI: 10.1203/00006450-200109000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quality of Energy Intake on Growth and Metabolic Response of Enterally Fed Low-Birth-Weight Infants

Abstract: Carbohydrate and fat may vary in their ability to support protein accretion and growth. If so, variations in the source of nonprotein energy might be used to therapeutic advantage in enterally fed low-birth-weight infants. To test the hypothesis that high-carbohydrate diets are more effective than isocaloric highfat diets in promoting growth and protein accretion, low-birthweight infants weighing 750 -1600 g at birth were randomized in a double blind study to receive one of five formulas differing only in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 36 publications
2
57
1
Order By: Relevance
“…Energy intakes necessary to promote optimal growth remain uncertain with recommendations varying from 110 to 135 kcal/kg/d (3). Further uncertainty exists with respect to the particular type of energy supplied, as studies have suggested that carbohydrate may be more effective than fat in enhancing growth and protein accretion (22). After discharge, lower protein densities appear adequate and although there appears to be no clear advantage to protein concentrations Ͼ2.7 g/100 kcal in the infants we studied, it has yet to be determined whether the smallest infants may themselves benefit.…”
Section: Protein Intakes In Preterm Infantsmentioning
confidence: 88%
“…Energy intakes necessary to promote optimal growth remain uncertain with recommendations varying from 110 to 135 kcal/kg/d (3). Further uncertainty exists with respect to the particular type of energy supplied, as studies have suggested that carbohydrate may be more effective than fat in enhancing growth and protein accretion (22). After discharge, lower protein densities appear adequate and although there appears to be no clear advantage to protein concentrations Ͼ2.7 g/100 kcal in the infants we studied, it has yet to be determined whether the smallest infants may themselves benefit.…”
Section: Protein Intakes In Preterm Infantsmentioning
confidence: 88%
“…This is easily achieved with fluid intakes of approximately 180 ml/kg/day (Kashyap et al, 2001). The analyzed non-supplemented preterm formulas contain between 71 and 81 kcal/100 ml, providing daily mean energy intakes between 107 and 122 kcal/kg with fluid intake of 150 ml/kg/day, but only 92.5-105.7 kcal/kg if fluid intake is restricted to 130 ml/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is unclear if carbohydrate-or fat-based calorie should be the main composite of non-protein calorie intake. Kashayp et al found challenging effects on the body composition of three study groups while varying the fat: carbohydrate ratio in an otherwise isocaloric and isoproteinic diet [7,8].…”
Section: What Is Appropriate Postnatal Growth?mentioning
confidence: 99%